2014
DOI: 10.1177/011719681402300304
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Immigrants in Korea: The Relationship between Interpersonal Communication and Acculturation

Abstract: Most studies on the acculturation of immigrants are based on the experiences of Hispanic, European, and Chinese immigrants in Western societies. Few studies have probed how attitudes are shaped among Asian immigrants in destination societies in Asia. This study deals with the acculturation processes of Chinese immigrants in Incheon Chinatown, Korea. The findings of the study support convergence and divergence strategies of acculturation. Another key finding is that Chinese immigrants who engage in interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The length of residence, the most commonly used proxy measure of acculturation, is associated with increased prevalence of CVD risk factors among immigrants in Western countries [ 1 , 3 , 6 , 7 ]. Little is known about the association between the length of residence of immigrants and CVD risks among new immigrants in the Republic of Korea (Korea) as most research has mainly focused on the acculturation of Hispanic, European, and Asian immigrants in Western societies [ 8 , 9 ]. Korea was mostly known for its large-scale emigration, however it has recently emerged as a popular destination for immigrants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The length of residence, the most commonly used proxy measure of acculturation, is associated with increased prevalence of CVD risk factors among immigrants in Western countries [ 1 , 3 , 6 , 7 ]. Little is known about the association between the length of residence of immigrants and CVD risks among new immigrants in the Republic of Korea (Korea) as most research has mainly focused on the acculturation of Hispanic, European, and Asian immigrants in Western societies [ 8 , 9 ]. Korea was mostly known for its large-scale emigration, however it has recently emerged as a popular destination for immigrants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the topic conversation of the local and refugees are existing on the casual matter such as culinary topic. Which actually done by Ethiopian immigrants who went to Israel reported that in daily coping immigrants embraced a perspective and attitude related to hosting effective norms [7].…”
Section: Cultural On the Patternmentioning
confidence: 99%